A renewable intelligent colorimetric indicator based on polyaniline for detecting freshness of tilapia. Issue 3 (27th December 2017) - Wang, Wenqi; Li, Min; Li, Houbin; Liu, Xinghai; Guo, Ting; Zhang, Guoquan; Xiong, Yabo
Abstract : A renewable indicator based on polyaniline (PANI) was developed and was able to indicate the freshness of tilapia. Hydrochloric acid was used in preparation of doped PANI, and experiments on colour variations of PANI films during spoilage of tilapia were conducted under accelerate storage condition (30°C) and chilled condition (4°C). When stored under 30°C, significant colour change of PANI film from green ( L * = 70, a * = −37, b * = 24) to peacock blue ( L * = 37, a * = −12, b * = −24) was shown when the amount of total volatile basic nitrogen (TVB‐N) (19.4 mg/100 g) was about to reach the critical value (20 mg/100 g). Similarly, when the TVB‐N reached 20.3 mg/100 g in chilled condition, the colour of PANI film also changed from green ( L * = 67, a * = −39, b * = 22) to peacock blue ( L * = 35, a * = −13, b * = −20). Importantly, renewed PANI film washed with hydrochloric acid also showed obvious colour variation from green to peacock blue when TVB‐N was around the critical value, and it could be recycled for at least 3 times. A proposed design of indicator based on PANI was given to help the consumers identify the freshness of tilapia and ensure that they get safe products. Abstract : A renewable indicator based on polyaniline (PANI) was developed and was able to be applied to intelligent packaging to indicate the freshness of tilapia. Significant colour change of PANI film from green to peacock blue was shown when the amount of total volatile basic nitrogen was about to reach the critical value (20 mg/100 g), and this PANI film could be recycled for at least 3 times. This renewable indicator is environmentally friendly and helps manufacturers reduce costs in production.